2006
DOI: 10.4028/www.scientific.net/msf.522-523.317
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation Behavior of Ru-Containing Ni-Base Single-Crystal Superalloys

Abstract: The 4th and advanced generation Ni-base single crystal superalloys, which contain large amounts of refractory metals for strengthening and platinum group metals, e.g., Ru, for TCP-phase prevention, show excellent high-temperature strengths. However, these alloying elements seem to decrease high-temperature oxidation resistance. In this study, Ni-base superalloys with various amounts of Ta, Re and Ru were examined in isothermal and cyclic exposures at 1373K to investigate the effect on the oxide growth rate and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 12 publications
0
35
0
Order By: Relevance
“…TCPs break up the rafted microstructure [2] and deplete the matrix of solid-solution strengtheners [3]. Although the effect of Ru on ''reverse partitioning'' is the subject of debate, its effect on oxidation performance has been reported only at higher temperatures, typically C1,000°C [4][5][6][7][8][9]. At these temperatures, non-protective oxides form together with sub-surface oxidation.…”
mentioning
confidence: 96%
“…TCPs break up the rafted microstructure [2] and deplete the matrix of solid-solution strengtheners [3]. Although the effect of Ru on ''reverse partitioning'' is the subject of debate, its effect on oxidation performance has been reported only at higher temperatures, typically C1,000°C [4][5][6][7][8][9]. At these temperatures, non-protective oxides form together with sub-surface oxidation.…”
mentioning
confidence: 96%
“…Alloy E in Figure 2(e) contains a relatively high amount of Co, and Alloy D in Figure 2(d) contains the second highest amount of Co, compared with the other alloys in group B. Co is known as an element that degrades the oxidation resistance of Ni-base superalloys, because CoO grows faster than NiO [34]. Kawagishi also reported that a high amount of Re in substrate degrades the oxidation resistance of Nibase superalloys [2]. High amounts of Re and Ru are generally present in the group B alloy.…”
Section: Discussionmentioning
confidence: 99%
“…Recent Ni-base superalloys incorporate refractory elements, and these superalloys can consist of more than 10 elements. The addition of refractory elements to Ni-base superalloys is imperative for maintaining excellent creep properties and microstructural stability at elevated temperature; however, the oxidation behavior of these latest Ni-base superalloys is more complex than was found in previous alloys [1][2][3] due to these additional elements.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations